Atomistic origins of Guinier-Preston zone formation and morphology in Al-Cu and Al-Ag alloys from first principles. (15th March 2019) - Nayak, Sanjeev K.; Hung, Cain J.; Hebert, Rainer J.; Alpay, S. Pamir
Abstract: Using first-principles computations we provide comprehensive energetics at zero Kelvin of Guinier-Preston zone (GPZ) formation and topologies of GPZs in two classical Al binaries: Al-Cu and Al-Ag. Without a priori geometric and morphological assumptions, we conclusively show that GPZs in Al-Cu prefer a planar arrangement of {100} layers while GPZs in Al-Ag consist of clusters with {111} facets. We expand the model to 34 additional elements from the fourth and the fifth rows of the periodic table. The morphologies can be entirely related to directional nature and hybridization of Al 3 s and 3 p orbitals in the presence of secondary elements. Graphical abstract: Unlabelled Image